Nanoscale Charge Heterogeneity and Chaotic Resistive Switching in Vo2-based Mott Memristors - Ojha, Pawan Kumar (IIT(BHU) Varanasi, 2024)
Abstract is available in the attachment.
Keywords: Material Science & Technology